2021
DOI: 10.3389/fpsyg.2021.657188
|View full text |Cite
|
Sign up to set email alerts
|

Playing Tetris Lets You Rate Odors as Less Intense

Abstract: Overweight and obesity are considered a huge problem in modern societies. Previous studies have shown that people who are regularly distracted by playing videogames or watching TV while eating are more likely to be overweight and that the number of people that are gaming worldwide is rising. Further, it has been established that both, watching TV or playing video games lead to an increased snack intake and a lower rating of perceived taste intensity. Since flavor perception is accomplished not only by the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Noteworthy, despite the wealth of studies, the understanding of how cognitive load impacts chemosensory perception remains fragmented and ambiguous. Adding to this body of knowledge, a recent study by Schadll et al 13 further substantiated the notion of changes in odor perception under conditions of distraction. Notably, this study advances the field by employing a more ecologically valid approach, utilizing a Tetris game as a means of cognitive load.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Noteworthy, despite the wealth of studies, the understanding of how cognitive load impacts chemosensory perception remains fragmented and ambiguous. Adding to this body of knowledge, a recent study by Schadll et al 13 further substantiated the notion of changes in odor perception under conditions of distraction. Notably, this study advances the field by employing a more ecologically valid approach, utilizing a Tetris game as a means of cognitive load.…”
Section: Introductionmentioning
confidence: 82%
“…The study employed the Tetris-game paradigm, as detailed by Schadll et al 13 , to serve as the cognitive distraction framework. This framework introduced two levels of cognitive load, categorized as low and high, which were created by varying the speed of falling blocks in the game.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, within the realm of olfaction, Hoffmann-Hensel et al (2017) (8) observed a decrease in the intensity of odors associated with low-caloric foods, while no discernible effect was noted for odors linked to high-caloric foods. Adding to this body of knowledge, a recent study by Schadll et al (2021) (9) further substantiated the notion of changes in odor perception under conditions of distraction. Notably, this study advances the eld by employing a more ecologically valid approach, utilizing a Tetris game as a means of cognitive load.…”
Section: Introductionmentioning
confidence: 88%
“…The study employed the Tetris-game paradigm, as detailed by Schadll et al (2021), to serve as the cognitive distraction framework. This framework introduced two levels of cognitive load, categorized as low and high, which were created by varying the speed of falling blocks in the game.…”
Section: Cognitive Distraction Taskmentioning
confidence: 99%